2022
DOI: 10.3390/f13070966
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity and Its Influencing Factors in a Subtropical Forest Community in China

Abstract: Functional diversity is considered a key link between ecosystem functions and biodiversity, and forms the basis for making community diversity conservation strategies. Here, we chose a subtropical forest community in China as the research object, which is unique in that other regions of the world at the same latitude have almost no vegetation cover. We measured 17 functional traits of 100 plant species and calculated seven different functional diversity indices, based on functional richness, evenness, and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…showed significant increases in soil macrofauna and biomass. The results of the present study also showed a significant positive correlation between soil biomass and Menhink and Margalef indices in Juniper stands during the growing season [31]. A significant positive correlation was also observed between Simpson index, Menhinick index, evenness and biomass in the Juniper stand during the resting season [22].…”
Section: Resultssupporting
confidence: 81%
“…showed significant increases in soil macrofauna and biomass. The results of the present study also showed a significant positive correlation between soil biomass and Menhink and Margalef indices in Juniper stands during the growing season [31]. A significant positive correlation was also observed between Simpson index, Menhinick index, evenness and biomass in the Juniper stand during the resting season [22].…”
Section: Resultssupporting
confidence: 81%
“…This is a relatively high species diversity given the small spatial coverage TA B L E 4 Generalised Linear Models' (GLM) significant differences among the bird species' functions based on feeding mode, and the body-size classes' distribution during different years of observations. of the four nature reserves that were sampled during the study, and it was matched by high functional richness which is reportedly positively correlated to the number of species (Li et al, 2022;Schleuter et al, 2010). However, Li et al (2022) reported an inverse relationship between species diversity and functional evenness and therefore, the moderate functional evenness across the nature reserves suggests stability of the biodiversity of the nature reserves since the high functional diversity increases habitat resilience in protected areas (Cottee-Jones et al, 2015;Lotz, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…The wood harvesting and invasion by alien plant species may partly create a favourable habitat mosaic for birds in the Eastern Cape Province (Leaver & Cherry, 2020), which partly could explain our results of relatively large numbers of bird species. This is a relatively high species diversity given the small spatial coverage of the four nature reserves that were sampled during the study, and it was matched by high functional richness which is reportedly positively correlated to the number of species (Li et al, 2022; Schleuter et al, 2010). However, Li et al (2022) reported an inverse relationship between species diversity and functional evenness and therefore, the moderate functional evenness across the nature reserves suggests stability of the biodiversity of the nature reserves since the high functional diversity increases habitat resilience in protected areas (Cottee‐Jones et al, 2015; Lotz, 2021).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations